Yams (Dioscorea spp.) in shellmounds and swiddens: ancient history in Babitonga Bay, Santa Catarina State, southern Brazil - Dalzemira Anselmo da Silva Souza; Dione Rocha da Bandeira; Nivaldo Peroni (Journal of Ethnobiology and Ethnomedicine, 2024)
Abstract Background In Babitonga Bay, southern Brazil, records of yam consumption exist among shellmound builders from at least 4000 years ago. Shellmounds (sambaquis) are anthropogenic structures in the form of mounds with layers of shells associated with other faunal remains, as well as with charcoal, artefacts and burial. Larger sambaquis are considered to be funerary monuments. The indigenous Jê and Guarani people also lived in the region before the European invasion and cultivated yams. Currently, exotic and domesticated yams are cultivated in the region by farmers. Our aim is to describe the long-term history between the people and Dioscorea in the Babitonga Bay region based on its consumption and occurrence in shellmounds and swiddens. Methods Surveys of Dioscorea spp. and host were carried out in the vegetation of shellmounds and in the surrounding area using visual detection through intensive searches in transects using the walking method. The survey of Dioscorea species used and cultivated in the precolonial, colonial and current periods was carried out based on the literature. In the present study, only Dioscorea trifida cultivations were recorded. Results Dioscorea cayennensis, Dioscorea chondrocarpa, Dioscorea dodecaneura, Dioscorea laxiflora, Dioscorea olfersiana, and Dioscorea scabra, all recorded in associated vegetation of shellmounds, in different combinations of the species. In swiddens, D. trifida is most common, followed by Dioscorea alata and, to a lesser extent, Dioscorea bulbifera and D. cayennensis. Records of food use prevail, but they are used as medicinal plants. Yams are integrated on anthropogenic soils of shellmounds and in swiddens in monoculture systems or in intercropping with Zea mays or Colocasia esculenta. The presence of exotic food trees and D. cayennensis in some shellmounds indicates the influence of colonizers on the composition of the vegetation. In sambaquis, there are overlapping processes of construction of cultural niches by different human groups at different times. Conclusions The sambaquis and the associated vegetation and swiddens form part of a domesticated landscape. The native species of Dioscorea recorded in shellmounds and surrounding vegetation do not depend on human action to perpetuate themselves in the environment. However, this does not rule out human influence in the past, but it does not indicate horticulture among the Sambaquianos. Greater investment in genetic, archaeobotanical and ethnobotanical research can contribute to a better understanding of the relationship between people and yams over thousands of years.